Studies on distribution of para-methoxymethamphetamine (PMMA) designer drug in rats using gas chromatography-mass spectrometry - Rohanova, Miroslava; Balikova, Marie (Legal medicine (Tokyo, Japan), 2009)
para-Methoxymethamphetamine (PMMA) is an abused psychedelic compound with reports of several intoxications and deaths after ingestion. However, its pharmacokinetics based on a controlled study is unknown and only partial information on its biotransformation is available. Our experimental study was designed for the time disposition profile of PMMA and its metabolites para-methoxyamphetamine (PMA), para-hydroxymethamphetamine (OH-MAM) and para-hydroxyamphetamine (OH-AM) in blood and biological tissues in rats after the bolus subcutaneous dose 40 mg/kg using a validated GC-MS method. The experimental results ascertained could be useful for subsequent evaluation of PMMA psychotropic or neurotoxic effects and the diagnostic concern of intoxication.
Keywords: játra; nové syntetické drogy; Lung; krysa rodu Rattus; zvířata; stimulanty centrálního nervového systému; plíce; potkani Wistar; methamfetamin; Brain Chemistry; mozek - chemie; soudní toxikologie; plynová chromatografie s hmotnostně spektrometrickou detekcí; Liver; Rats, Wistar; Male; Forensic Toxicology; Rats; Animals; Central Nervous System Stimulants; Designer Drugs; mužské pohlaví; Gas Chromatography-Mass Spectrometry; Methamphetamine